Pengaruh Metode Mind Map dengan Media Komik terhadap Minat Baca dan Hasil Belajar Kognitif Siswa - Pramana, Ida Bagus Wika; Fitriani, Herdiyana; Safnowandi, Safnowandi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
The main problem in learning in formal education (schools) today is the low quality of student learning. One of the factors is the teacher's ability to manage, develop methods and select learning media. In this case the researcher tried to use the mind map method with comic media. This study aims to determine the effect of the mind map method with comic media on reading interest and cognitive learning outcomes of class VIII students in biology science subjects at SMPN 10 Mataram. This type of research is a quasi-experimental. The population in this study were all eighth grade students of SMPN 10 Mataram. This sample was taken using a simple random sampling technique, namely class VIII F as the experimental class and class VIII G as the control class. Data collection in this study was taken by giving pre-test and post-test to the sample class students. Data collection techniques using a reading interest questionnaire and objective tests that have been tested for validity and reliability. Based on the results of the study showed that the students' reading interest obtained an average of 60.54 for the experimental class with a percentage of 75.67%, while the control class was 51.79 with a percentage of 64.74% which indicated that students were included in the interested category, indicating that the reading interest of students who using the mind map method with comic media is higher than the reading interest of students who use conventional methods. Based on the results of the study, it was shown that the pre-test data obtained an average value of 51.03 for the experimental class and 51.55 for the control class. The post-test results showed an average of 77.93 for the experimental class and 68.96 for the control group. The post-test data of the sample class students were analyzed using t-test. Based on the results of data analysis using t-test obtained t count > t table, which is 4.33 > 2.00 at an error level of 5%. This indicates that the mind map method with comic media has an effect on cognitive learning outcomes for class VIII students in biology science subjects. at SMPN 10 Mataram.